Replication protein A large subunit (RPA1a) limits chiasma formation during rice meiosis. Issue 3 (7th August 2021) - Miao, Yongjie; Shi, Wenqing; Wang, Hongjun; Xue, Zhihui; You, Hanli; Zhang, Fanfan; Du, Guijie; Tang, Ding; Li, Yafei; Shen, Yi; Cheng, Zhukuan
Abstract: Replication protein A (RPA), a single-stranded DNA-binding protein, plays essential role in homologous recombination. However, because deletion of RPA causes embryonic lethality in mammals, the exact function of RPA in meiosis remains unclear. In this study, we generated an rpa1a mutant using CRISPR/Cas9 technology and explored its function in rice ( Oryza sativa ) meiosis. In rpa1a, 12 bivalents were formed at metaphase I, just like in wild-type, but chromosome fragmentations were consistently observed at anaphase I. Fluorescence in situ hybridization assays indicated that these fragmentations were due to the failure of the recombination intermediates to resolve. Importantly, the mutant had a highly elevated chiasma number, and loss of RPA1a could completely restore the 12 bivalent formations in the zmm (for ZIP1-4, MSH4/5, and MER3) mutant background. Protein–protein interaction assays showed that RPA1a formed a complex with the methyl methansulfonate and UV sensitive 81 (and the Fanconi anemia complementation group M–Bloom syndrome protein homologs (RECQ4A)–Topoisomerase3α–RecQ-mediated genome instability 1 complex to regulate chiasma formation and processing of the recombination intermediates. Thus, our data establish a pivotal role for RPA1a in promoting the accurate resolution of recombination intermediates and in limiting redundant chiasma formation during rice meiosis. Abstract : RPA1a guarantees accurate meiotic recombination during rice gametogenesis, and acts as a guard to prevent excessive meiotic crossovers.